2022
DOI: 10.3390/ijerph191912030
|View full text |Cite
|
Sign up to set email alerts
|

UK Doctors Delivering Physical Activity Advice: What Are the Challenges and Possible Solutions? A Qualitative Study

Abstract: Despite strategies to enable Health Care Professionals (HCPs) to give physical activity (PA) advice to patients, this appears to be rarely done in consultations. The aims of the present study were to gain an understanding of doctors’ awareness of current PA guidelines and to explore their opinions on barriers and solutions. A qualitative approach using semi-structured interviews was adopted. This study included 15 doctors currently working in the UK’s National Health Service (NHS). A thematic analysis approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 31 publications
0
16
0
3
Order By: Relevance
“…Awareness of the CMO PA guidelines was also recently reported to be limited in a qualitative study of 15 general practitioners (GPs) by Vishnubala et al . 22 Another larger study in 2016 of 1013 GPs found that 30% had never heard of the CMO PA guidelines and a further 50% had heard of them but were very unfamiliar. 27 Arguably, the lack of awareness of the CMO PA guidelines could be a result of HCPs using alternative PA guidelines, with some participants in this study reporting using the WHO guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Awareness of the CMO PA guidelines was also recently reported to be limited in a qualitative study of 15 general practitioners (GPs) by Vishnubala et al . 22 Another larger study in 2016 of 1013 GPs found that 30% had never heard of the CMO PA guidelines and a further 50% had heard of them but were very unfamiliar. 27 Arguably, the lack of awareness of the CMO PA guidelines could be a result of HCPs using alternative PA guidelines, with some participants in this study reporting using the WHO guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews adopted a semistructured design, which is a common method in healthcare research, 20 to encourage open-ended responses that could be elaborated on with probing for the limited responses, which explores participants’ thoughts and beliefs. 21 The interview guide was created by Vishnubala et al 22 and adapted to make questions specific to physiotherapists (see online supplemental file ). The guide included 30 interview questions, split into 5 sections: (1) demographics, (2) PA knowledge and education, (3) resources and interventions, (4) COVID-19 and (5) other, providing an opportunity for the participants to express any other thoughts or ideas that emerged during the interview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Moreover, practitioners point towards the need for more individualised approaches for PA guidance that use resources effectively. 21 Interventions to increase knowledge on how and why to engage in PA may not be enough.…”
Section: Discussionmentioning
confidence: 99%
“…This refers to the behaviour change framework of capability (skills and capacity for movement), opportunity and motivation (opportunities, motivations and barriers for movement) 20 ; with additional aspects of guidance, structure and permission not to push oneself too hard (a personalised, safe space in which to develop), that participants felt enabled a protective and beneficial effect. 21 and a small effect that likely wanes over time. 22 Moreover, practitioners point towards the need for more individualised approaches for PA guidance that use resources effectively.…”
Section: Key Findingsmentioning
confidence: 98%